CUTTING EDGE RESEARCH METHODS IN HOSPITALITY AND TOURISM (EMERALD GROUP PUBL, 2023)
Cutting Edge Research Methods in Hospitality and Tourism sits at the forefront of fast-paced developments in the tourism and hospitality industry, highlighting the importance of applied and pure research to address the theoretical and practical problems and gaps.